Origin and development of Buddhist images - Srivastava, Kamal Shankar (New Delhi, 2007)
All the three religious systems of India, Hinduism, Buddhism and Jainism developed well filled pantheons, and it is not always easy to decide to which of these three systems a particular image should be assigned.It is observed that a free interchange of deities actually took place at the very outset of Buddhism and Jainism an in more promiscuous Tantric Age.
Keywords: Buddhist art - India - History